Medical Physics and General Physics for Healthcare Technology - Hamza, Hamza Amin; jaber, Jaafar Muhammad; Attea, Attea Awaid; Salman, Imam Ali; Ghareeb, Meaad Hadi (American Journal of Botany and Bioengineering, 2025)
The medical physics profession is characterized by a long history of formal education, a structured training program, and appropriate local accreditation of medical physicists. Although the many medical societies around the world have been persistently promoting the establishment of a more structured education and training program in medical physics, progress has been slow due to the heavy workload from clinical duties and the consequent shortage of locally available instructors in this complicated field. Advances in communications technologies have the potential to overcome many of these hurdles and help graduate and even undergraduate MP courses reach a wider audience. Medical physicists with good teaching knowledge and skills will be recruited as part-time online instructor collaborators. Courses can be conducted using live video/audio/graphics teleteaching with audience interaction. The implementation of online courses should serve as a springboard for further development of video/audio taped on-demand courses and/or e-Learning. Low-cost video/audio equipment for local recording and broadcasting as well as the necessary supporting facilities for the preparation of high-quality multimedia-learning material for on-demand courses are also discussed. The teaching of medical physics is very different from general physics. Medical physics is not just ‘physics’ applied to medicine and healthcare technology; medical physicists need a distinctly different training from that of a physicist. Courses on medical physics must therefore not only teach the principles of the techniques and applications of ionizing radiation, including radiation therapy, diagnostics, imaging, safety, biophysics, etc., but also teach topics on biomedical engineering and nonionizing radiation. The avowed biomedical engineering department of a university would not have a group of medical physics instructors. With progress in imaging, radiation dosimetry and protection, teletherapy, and treatment planning, modeling and computations of dose distributions and radioactive dose delivery may have to be taught by engineers rather than physicists.